Effects of High-Velocity Resistance Training on Athletic Performance in Prepuberal Male Soccer Athletes. Issue 12 (December 2016) - Negra, Yassine; Chaabene, Helmi; Hammami, Mehréz; Hachana, Younés; Granacher, Urs
Abstract: Negra, Y, Chaabene, H, Hammami, M, Hachana, Y, and Granacher, U. Effects of high-velocity resistance training on athletic performance in prepuberal male soccer athletes. J Strength Cond Res 30(12): 3290–3297, 2016—The aim of this study was to assess the effectiveness of a 12-week in-season low-to-moderate load high-velocity resistance training (HVRT) in addition to soccer training as compared with soccer training only on proxies of athletic performance in prepubertal soccer players. Twenty-four male soccer players performed 2 different protocols: (a) regular soccer training with 5 sessions per week ( n = 11; age = 12.7 ± 0.3 years) and (b) regular soccer training with 3 sessions per week and HVRT with 2 sessions per week ( n = 13; age = 12.8 ± 0.2 years). The outcome measures included tests for the assessment of muscle strength (e.g., 1 repetition maximum [1RM] half-squat tests), jump ability (e.g., countermovement jump, squat jump [SJ], standing long jump [SLJ], and multiple 5-bound tests [MB5s]), linear speed (e.g., 5-, 10-, 20-, and 30-m sprint tests), and change of direction (e.g., T-test and Illinois change of direction test). Results revealed significant group × test interactions for the SJ test ( p ≤ 0.05, d = 0.59) and the SLJ test ( p < 0.01, d = 0.83). Post hoc tests illustrated significant pre-post changes in the HVRT group (SJ: ∆22%, p < 0.001, d = 1.26; SLJ: ∆15%, p < 0.001, d = 1.30) but not in the control group. In addition, tendencies toward significant interaction effects were found for the 1RM half-squat ( p = 0.08, d = 0.54) and the 10-m sprint test ( p = 0.06, d = 0.57). Significant pre-post changes were found for both parameters in the HVRT group only (1RM: ∆25%, p < 0.001, d = 1.23; 10-m sprint: ∆7%, p < 0.0001, d = 1.47). In summary, in-season low-to-moderate load HVRT conducted in combination with regular soccer training is a safe and feasible intervention that has positive effects on maximal strength, vertical and horizontal jump and sprint performance as compared with soccer training only.